Food expenditure patterns and dietary diversity in Nepal: Is dietary quality improving? - Kumar, Anjani; Thapa, Ganesh B.; Joshi, Pramod Kumar (International Food Policy Research Institute, 2017)
The paper measures dietary diversity among different income groups in Nepal and identifies the drivers of this diversity as a first step toward addressing the widespread prevalence of nutrient deficiency. The level of diversity in household diets is an indirect measure of dietary quality and the extent to which the nutritional needs of households are being met. However, there is limited understanding of the trends, patterns, and determinants of dietary diversity in Nepal. This study is an attempt to enrich the literature on this issue. Drawing on unit-level data from three rounds (1995, 2004, and 2011) of the Nepal Living Standards Survey (NLSS), we use multilevel modeling, quantile regression, and the Blinder-Oaxaca decomposition method to decipher the trends, determinants, and drivers of dietary diversity in Nepal. Our study finds that changes in household sociodemographic and agricultural characteristics are very important in explaining the improvement in dietary quality. Changes in household characteristics account for at least 37 percent of the observed improvement, and agriculture-related changes explain at least 16 percent of the observed improvement. Variables positively associated with dietary quality are remittances, social cash transfers, parents’ education, crop diversity, access to markets and paved roads, and ownership of a television and telephone, among others. Our findings are highly robust across the different model specifications. Our study concludes by calling for a multisectoral approach to tackle nutrition issues in Nepal.